Investigation into Microstructure Evolution of Co–Ni–Cr–W–Based Superalloy During Hot Deformation - Zhang, Wei; Zhu, Baohong; Wu, Shuaishuai; Tao, Shutian (Frontiers in Materials, 2021)
Hot compression tests were conducted using Gleeble-3500 thermomechanical simulator at temperatures ranging from 1000 ℃ to 1200 ℃ with the strain rate ranging from 0.1 s-1 to 10 s-1. Electron backscatter diffraction (EBSD) technique were employed by investigating the microstructure evolution during hot deformation. Microstructure observations reveal that deformation temperatures and strain rates have a significant effect on the DRX process. It is found that the fraction and grain size of DRX increases with the increase of deformation temperature, along with the increasing of high-angle boundaries （HAGBs）. The fraction of DRX first decreases and then increases with the increase of strain rates. It is noted that there are both the nucleation mechanisms of discontinuous dynamic recrystallization (DDRX) and continuous dynamic recrystallization (CDRX) during DRX process for Co-Ni-Cr-W-based superalloy. DDRX and CDRX are the primary and subsidiary nucleation mechanism of DRX, respectively. It is also found that deformation temperatures and strain rates have almost no effect on the primary and subsidiary nucleation mechanism of DRX. At the temperature above 1150 ◦C, the complete DRX occurred with the average grain sizes about 25.32-29.01μm. The homogeneity and refinement of microstructure can be obtained by selecting the suitable hot deformation parameters.